Profile of Problem Solving and Student Learning Motivation in Science Learning Material on Motion and Force at SMPN 5 Randublatung Satu Atap - Karyawan; Siti Patonah; Mega Novita (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to determine students' problem-solving abilities and learning motivation on Motion and Force material. The method in this research uses a qualitative descriptive approach with the subjects used being 18 grade 7 students of SMPN 5 Randublatung Satu Atap, totaling 18 people. To measure students' learning motivation and ability to solve problems. The research results show that the level of student motivation in learning movement and style still varies (high, medium and low). As many as 53% of students have a high level of motivation (scores 54-65); as many as 37% of students have a moderate level of motivation (scores 35-53); and as many as 10% of students have a low level of motivation (score 24-34). The ability to solve problems obtained results in the form of the lowest score of 15, the highest of 45, and the average in one class was 38. The research results showed that students did not understand the material of motion and force. This can be seen from the results of the questionnaire data and questions.